Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 + 2i)z – (4 + 7i) = 2 – 5i
⇔(3+2i)z=6+2i
<=> z = \(\dfrac{\text{6 + 2 i}}{\text{3 + 2 i}}\) = \(\dfrac{22}{13}\) - \(\dfrac{6}{13}\)i
b) (7 – 3i)z + (2 + 3i) = (5 – 4i)z
⇔(7−3i−5+4i)=−2−3i
⇔z= \(\dfrac{\text{− 2 − 3 i}}{\text{2 + i}}\) = \(\dfrac{-7}{5}\) - \(\dfrac{4}{5}i\)
c) z2 – 2z + 13 = 0
⇔ (z – 1)2 = -12 ⇔ z = 1 ± 2 √3 i
d) z4 – z2 – 6 = 0
⇔ (z2 – 3)(z2 + 2) = 0
⇔ z ∈ { √3, - √3, √2i, - √2i}
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 + 4i)z = (2 + 5i) – (1 – 3i) = 1 + 8i
Vậy z=1+8i3+4i=(1+8i)(3−4i)25=3525+2025i=75+45iz=1+8i3+4i=(1+8i)(3−4i)25=3525+2025i=75+45i
b) (4 + 7i)z – (5 – 2i) = 6iz ⇔ (4 + 7i)z – 6iz = 5 – 2i
⇔ (4 + i)z = 5 – 2i
⇔z=5−2i4+i=(5−2i)(4−i)17⇔z=1817−1317i
![](https://rs.olm.vn/images/avt/0.png?1311)
a) đặc : \(x=a+bi\) với \(a;b\in R\) và \(i^2=-1\)
ta có : \(\left(1+2i\right)x-4\left(4-5i\right)=-7+3i\)
\(\Leftrightarrow\left(1+2i\right)\left(a+bi\right)-4\left(4-5i\right)=-7+3i\)
\(\Leftrightarrow a-2b+2ai+bi-16+20i=-7+3i\)
\(\Leftrightarrow\left(a-2b-16\right)+\left(2a+b+20\right)i=-7+3i\)
\(\Leftrightarrow\left\{{}\begin{matrix}a-2b-16=-7\\2a+b+20=3\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}a-2b=9\\2a+b=-17\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}a=-5\\b=-7\end{matrix}\right.\) vậy \(x=-5-7i\)
câu b lm tương tự nha .
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 - 2i)(2 - 3i) = (6 - 6) + (-9 -4)i = -13i;
b) (-1 + i)(3 + 7i) = (-3 - 7) + (-7 + 3)i = -10 -4i;
c) 5(4 + 3i) = 20 + 15i;
d) (-2 - 5i).4i = -8i - 20i2 = -8i -20(-1) = 20 - 8i
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 + 2i)[(2 – i) + (3 – 2i)]
= (3 + 2i)(5 – 3i) = 21 + i
b)(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i
c) (1 + i)2 – (1 - i)2 = 2i – (-2i) = 4i
d) 3+i2+i−4−3i2−i=(3+i)(2−i)5−(4−3i)(2+i)5=7−i5−11−2i5=−45+15i
a) Ta có (3 - 2i)z + (4 + 5i) = 7 + 3i <=> (3 - 2i)z = 7 + 3i - 4 - 5i
<=> z =
<=> z = 1. Vậy z = 1.
b) Ta có (1 + 3i)z - (2 + 5i) = (2 + i)z <=> (1 + 3i)z -(2 + i)z = (2 + 5i)
<=> (1 + 3i - 2 - i)z = 2 + 5i <=> (-1 + 2i)z = 2 + 5i
z =![This is the rendered form of the equation. You can not edit this directly. Right click will give you the option to save the image, and in most browsers you can drag the image onto your desktop or another program.](http://latex.codecogs.com/gif.latex?%5Cdpi%7B80%7D%20%5Cfrac%7B2%20+%205i%7D%7B-1+2i%7D%3D%5Cfrac%7B%282+5i%29%28-1-2i%29%7D%7B5%7D%3D%5Cfrac%7B-2-4i-5i-10i%5E%7B2%7D%7D%7B5%7D%3D%5Cfrac%7B8-9i%7D%7B5%7D%3D%5Cfrac%7B8%7D%7B5%7D-%5Cfrac%7B9%7D%7B5%7Di)
Vậy z =![This is the rendered form of the equation. You can not edit this directly. Right click will give you the option to save the image, and in most browsers you can drag the image onto your desktop or another program.](http://latex.codecogs.com/gif.latex?%5Cdpi%7B80%7D%20%5Cfrac%7B8%7D%7B5%7D-%5Cfrac%7B9%7D%7B5%7Di)
c) Ta có
+ (2 - 3i) = 5 - 2i <=>
= 5 - 2i - 2 + 3i
<=> z = (3 + i)(4 - 3i) <=> z = 12 + 3 + (-9 + 4)i <=> z = 15 -5i